(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Description of clinical and subclinical characteristics of pneumococcal pneumonia in children under 5 years old at Nghe An Obstetrics and Pediatrics; evaluation of treatment results of pneumococcal pneumonia in children under 5 years old at Nghe An Obstetrics and Pediatrics Hospital. Patients and Methods: Pediatric patients diagnosed with pneumococcal pneumonia, from 2 to 60 months of age, were treated at Nghe An Obstetrics and Pediatrics Hospital, cross-sectional descriptive study. Result: The most common clinical symptoms were cough, fever and moist crackles with the corresponding rated of 98.45%, 77.72% and 93.26%. The rate of leukocytosis was 45.08%, CRP increase was 43.52%. On X-ray film, 89.64% had bronchopneumonia. 100% of children used antibiotics in treatment, of which 80.6% received antibiotics before the vailable antibiotic chart. Over 95% of pneumococcal strains were susceptible to linezolid, levofloxacin, vancomycin, rifampicin, chloramphenicol and moxifloxacin. Pneumococcal resistanced to macrolide antibiotics is very common (> 98%). The rate of reduced sensitivity to beta-lactam antibiotics was quite high (> 50%). The average number of days of treatment was 8.46 ± 4.12. The rate of children recovering from the disease reached 68.91% and no deaths. Conclusion: The most common clinical symptoms were cough, fever and moist crackles with the corresponding rated of 98.45%, 77.72% and 93.26%. The rate of leukocytosis was 45.08%, CRP increase was 43.52%. On X-ray film, 89.64% had bronchopneumonia. Over 95% of pneumococcal strains were susceptibled to linezolid, levofloxacin, vancomycin, rifampicin, chloramphenicol and moxifloxacin. Pneumococcal resistanced to macrolide antibiotics is very common (> 98%). The rate of reduced sensitivity to beta-lactam antibiotics was quite high (> 50%). The rate of children recovering from the disease reached 68.91% and there were no deaths.